Pengaruh Minat Baca Terhadap Kemampuan Literasi Awal Pada Anak Usia 5-6 Tahun di TK Se-Kabupaten Temanggung - Solichatul Wahyu Wulandari; Intan Puspitasari (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
The importance of early literacy skills is useful to make it easier for a child to master literacy activity at a later stage. Some studies show that early literacy is related to a child's interest in reading from an early age. The literacy and parenting environment of parents has an important role to play in the emergence of a child's reading interest that subsequently promotes reading competence. Research on early literacy is still rare in early childhood in Temanggung district. This study aims to find out the influence between reading interests on early literacy skills of children aged 5-6 years in Se-Kab District Temanggung. The type of research is quantitative correlational. The sampling technique uses Simple Random Sampling with a sample of 60 children. The research data was obtained from a survey questionnaire namely Children's Reading Interest Scale and Early Childhood Early Literacy Skill Scale. Data analysis techniques are simple linear regression. The results of the study show that there is a positive influence between the interest in reading and the early literacy skills of 5-6year-olds in a Temanggung district high school. Simultaneously, reading interests were influenced by 35.9% of early literacy and the rest were influenced by other variables not included in the study. It can then be concluded that if the interest in reading increases then early literacy also improves.